Influencing factors of maternal online health information-seeking behavior - Huajie Xu; Yanping Zhou; Xiaotong Wang (Frontiers in Public Health)
IntroductionAs an important social group, mothers possess unique physiological and psychological characteristics. They may rely on Internet sources for obtaining health information about themselves and their children.MethodsBased on the Elaboration Likelihood Model (ELM) and Technology Acceptance Model (TAM), the influencing factors model of maternal online health information searching behavior is constructed. We collect 903 valid sample data through the questionnaire survey in China. Using SPSS software to empirically analyze the influence of different influencing factors on maternal online health information searching behavior.ResultsPerceived usefulness mediated between the Internet information quality and online health information-seeking behavior, accounting for 59.46% of the variance. Anxiety mediated between maternal stress and online health information-seeking behavior, accounting for 19.40% of the variance.ConclusionInternet information quality positively affected mothers’ perception of the usefulness of the information. Perceived usefulness and anxiety played a partial mediating role in the central and peripheral paths, respectively. Furthermore, social support effectively moderated the influence of maternal stress on their anxiety.